Application of Rambutan Honey Toothpaste with Color Indicator Effect on Salivary Malondialdehyde Levels - Yuslianti, Euis Reni; Widyasari, Ratih; Arif, Bayu Syamsul (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2024)
Oxidative stress in the oral cavity, driven by an imbalance between free radicals and antioxidants, can lead to lipid peroxidation, as reflected by elevated malondialdehyde (MDA) levels in saliva. Proper oral hygiene, such as regular tooth brushing, is vital in mitigating oxidative damage. This study aimed to evaluate the effects of rambutan honey toothpaste with a color indicator on reducing oxidative stress in the oral cavity by measuring salivary MDA levels. This research was conducted using a laboratory experimental design, with saliva samples collected from students at the Faculty of Dentistry, Universitas Jenderal Achmad Yani. Participants were assigned to five groups: rambutan honey toothpaste with a color indicator (RHTCI), rambutan honey toothpaste without a color indicator (RHT), color-indicated toothpaste without honey (TCI), base toothpaste (BT), and distilled water (DW). The thiobarbituric acid reactive substances (TBARs) method was applied to assess MDA levels, and statistical analysis was conducted using Kruskal-Wallis and Mann-Whitney tests. The results showed a significant reduction in salivary MDA levels following the use of RHTCI (p = 0.0001). A notable difference was also found between RHTCI and TCI (p = 0.001), while no significant difference was observed between RHTCI and RHT (p = 0.190). These findings suggest that rambutan honey toothpaste with a color indicator effectively reduces salivary MDA levels, highlighting its potential antioxidant benefits.